Angers/Iuliomagus, cité des Andécaves, et Le Mans/Vindinum, cité des Cénomans : deux capitales, deux modes de déploiement urbain - Pierre Chevet; Martin Pithon (Gallia)
Iuliomagus and Vindinum, two neighbouring civitas-capitals, witnessed urban development with two very different dynamics, highlighting distinct conditions of development. While the first underwent from the 20s AD a massive urban restructuring arranged within an orthogonal street-grid covering 90 ha. and created in ten years, completely freed of topographical constraints, the second showed a more gradual development, with the laying out of the street-grid extending between 30 and 60-70 AD, with topographical adaptations and programmes to remodel the relief lasting throughout the 1st c. AD at least.These contrasting modes of development created very different urban landscapes. The site at Angers’ which resulted from an overall plan prepared ahead of time and implemented rapidly, presented a ‘frontage urbanism’ apparently uniform and rigid, but it conserved, in the interior of the insulae and at the outskirts, the axes of earlier lay-outs. On the other hand, Le Mans seems to expand and develop without any overall strategy, witnessing a more gradual transformation which seems to have had a profound impact, erasing every trace of any earlier urban landscape. The causes that determined such differing urban development remain an open question. One hypothesis could be based on clear support or strong pressure from the Roman central administration that could have favoured or imposed such a restructuring on Angers. Whatever the political or military motives, they apparently did not apply in Le Mans, where more local demographic and economic needs undoubtedly predominated.